Respuesta :

Answer:

B. √3/2

Step-by-step explanation:

Sin[sin⁻¹ (√3/2)]

sin⁻¹ (√3/2 = 60°

60° is the acute angle, in the first quadrant

Therefore;

Sin[sin⁻¹ (√3/2)] = sin 60° ; since sin⁻¹ (√3/2 = 60°

Sin 60° = √3/2

Therefore, the answer = √3/2

Answer:

B)  [tex]\frac{\sqrt{3}}{2}[/tex].

Step-by-step explanation:

Given : [tex]sin(sin^{-1}(\frac{\sqrt{3}}{2})[/tex].

To find : Evaluate.

Solution : We have given

[tex]sin(sin^{-1}(\frac{\sqrt{3}}{2})[/tex].

By the identity : [tex]sin(sin^{-1}(x)[/tex] = x .

Here, x = [tex]\frac{\sqrt{3}}{2}[/tex].

So, [tex]sin(sin^{-1}(\frac{\sqrt{3}}{2})[/tex] =  [tex]\frac{\sqrt{3}}{2}[/tex].

Therefore, B)  [tex]\frac{\sqrt{3}}{2}[/tex].